The complete mitochondrial genome of Pardosa pusiola (Araneae, Lycosidae) and its phylogenetic implications. Issue 4 (16th April 2023) - Yi, Jiequn; Liu, Min; Liu, Jianbai; Mao, Yongkai; Lin, Mingjiang; Xu, Hanliang; An, Yuxing; Wu, Han; Li, Jihu
Abstract: The mitochondrial genome (mitogenome) is useful for identification and phylogenetic analyses among arthropods, but there are no sufficient mitogenome data for wolf spiders. To enrich the mitogenome database of wolf spiders, the complete mitogenome of Pardosa pusiola was sequenced by high‐throughput sequencing. It is 14, 284 bp, comprising 13 protein‐coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and a control region (CR). It represents a high bias toward A and T nucleotides with an A + T content of 76.49%. The mitogenome exhibited a negative AT skew (−0.13) and a positive GC skew (0.32). Most PCGs started with ATN codons and ended with TAA, TAG, or an incomplete T. In addition, most tRNAs had aberrant secondary structures with the absence of DHU arm or TΨC arm. Analysis performed with CREx software demonstrated that large‐scale rearrangements of tRNAs were observed in the mitogenome of P. pusiola as compared with the putative ancestral mitogenome. The Bayesian inference (BI) and maximum likelihood (ML) phylogenetic trees based on the 13 PCGs of 25 spiders had the same topology, which could be presented as (Araneidae + (Agelenidae + (Dictynidae + Desidae)) + (Salticidae + (Thomisidae + (Oxyopidae + (Pisauridae + Lycosidae))))). This study offers a useful genetic resource for the taxonomy and phylogeny of spiders.